Image preprocessing for light field imaging applications - G. Deepika (2014)
Over the years, there has been an increasing problem of focusing of images in conventional photography. The main reason for this can be attributed to the fact that much information is lost when a picture is taken in a conventional camera. Light field imaging can be used to address this issue as it captures information about the direction of individual rays of light hitting its many micro-sensors.